Chronotherapeutic Press-Coated Tablets of Tramadol Hydrochloride: In Vivo Evaluation - Talakoti, Ramya Krishna (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The purpose of this study is to conduct in vivo pharmacokinetic study of Tramadol Hydrochloride (TH) press-coated tablets (PCTs) in rabbit plasma using reversed-phase high-performance liquid chromatography (RP-HPLC) technique. Materials and Methods: A Phenomenex bond clone reverse phase C18 (4.6 × 150 mm, 5μm) column and mobile phase acetonitrile – 0.01 M phosphate buffer (30:70% v/v) containing 0.1 % triethylamine with 1 ml/min flow rate were used for development and validation of RP-HPLC method, further used to calculate various pharmacokinetic parameters of TH core tablets and PCT in rabbits which received TH core and PCTs. Results and Discussion: The developed method showed a linearity in range of 10–800 ng/ml (r2 = 0.9997), good precision and accuracy with acceptable relative standard deviation values, repeatability, and reproducibility. The drug TH extracted with recovery in range of 96.20–98.29%. The pharmacokinetic study of PCT showed 5 h lag time with drug release. The Cmax and Tmax of core tablet and PCTs were 409.86 ± 40.46 ng/ml at 0.75 h and 289.46 ± 32.58 ng/ml at 10 h, respectively. Area under curve(0-t) of core and PCTs was 1531.26 ± 499.09 ngh/ml and 2293.48 ± 521.8 ngh/ml, respectively. Conclusion: Based on results, PCTs provided better chronotherapeutic release characteristics with drug release after a specified lag time using polymer blend of HPMC E50 and HPMC E100 as release modifiers for therapy of Rheumatoid arthritis.